IMPROVING PHYSICAL EDUCATION OF STUDENTS WITH FATIGUED HEALTH - Muminov Sherzod Ilyosovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article deals with the issues of physical culture and sports presented in higher educational institutions as an academic discipline and the most important component of the holistic development of personality. It promotes the harmonization of bodily and spiritual unity, provides the biological potential of the vital activity of the organism, and promotes the manifestation of a high level of social activity and creative attitude to activity.